The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/horticulturae8100954
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1−MCP on Storage Quality and Enzyme Activity of Petals of Edible Rose Cultivar ‘Dianhong’ at Low Temperatures

Abstract: To explore the effect of 1-methylcyclopropene (1−MCP) on the storage quality of edible roses, flowers of the edible rose variety ‘Dianhong’ were used as materials to study the effect of post-harvest 1−MCP fumigation (concentration of 30 μL/L). The measures included respiration intensity, water loss rate, antioxidant-related substance content (soluble sugar, crude fibre, AsA, anthocyanin, total phenols and MDA), enzyme activity (SOD, CAT, APX, PAL and PPO) and petal appearance quality in different storage perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The clearance of ROS in the cells mainly relies on the action of non-enzymatic antioxidants and antioxidant enzymes. For example, 1-MCP treatment can inhibit the respiratory metabolism of edible roses while increasing the content of total phenols and anthocyanins and the activity of SOD and CAT to maintain storage quality [31]. There are similar conclusions in the study of ginger storage [32].…”
Section: Discussionmentioning
confidence: 65%
“…The clearance of ROS in the cells mainly relies on the action of non-enzymatic antioxidants and antioxidant enzymes. For example, 1-MCP treatment can inhibit the respiratory metabolism of edible roses while increasing the content of total phenols and anthocyanins and the activity of SOD and CAT to maintain storage quality [31]. There are similar conclusions in the study of ginger storage [32].…”
Section: Discussionmentioning
confidence: 65%
“…Wills et al [15] fumigated mature tomatoes with 5.0-100.0 µL/L 1-MCP, effectively extending their postharvest storage period, and exposure to 20.0 µL/L 1-MCP increased the postharvest life of tomatoes by 25%. It has also been found that a high-dose 1-MCP (30.0 µL/L) fumigation treatment enhances antioxidant capacity in newly harvested rose petals [16]. Furthermore, 1-MCP showcases the virtues of being non-toxic, remarkably efficacious, and devoid of residues [17].…”
Section: Introductionmentioning
confidence: 95%